2011
DOI: 10.1111/j.1365-2214.2011.01278.x
|View full text |Cite
|
Sign up to set email alerts
|

Accidental injuries are more common in children with attention deficit hyperactivity disorder compared with their non‐affected siblings

Abstract: School-aged children with ADHD are at higher risk of accidental injuries than their non-ADHD siblings, regardless of ADHD subtype, co-morbid psychiatric conditions, developmental co-ordination problems and environmental/familial conditions. Awareness and adequate education of parents and caregivers of children with ADHD concerning the increased injury risks are thus warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 21 publications
1
27
0
2
Order By: Relevance
“…et al have not found any statistically significant correlation between hyperactivity/impulsivity scores and unwanted accidents though they have found significant correlation between attention deficit and accidents (11). Our results and literature data point to the idea that attention deficit is associated with undesirable accidents although intra-articular bleeding in haemophilia patients is more related to bumps and falls due to extreme mobility of these children.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…et al have not found any statistically significant correlation between hyperactivity/impulsivity scores and unwanted accidents though they have found significant correlation between attention deficit and accidents (11). Our results and literature data point to the idea that attention deficit is associated with undesirable accidents although intra-articular bleeding in haemophilia patients is more related to bumps and falls due to extreme mobility of these children.…”
Section: Discussionsupporting
confidence: 56%
“…It has often been reported that children diagnosed with ADHD have a more higher rate of getting injured due to frequent accidents (10)(11)(12)(13)(14)(15)(16)(17). The fact that children with ADHD suffer injuries due to frequent accidents has recurrently been associated with attention deficiency, hyperactivity, and impulsivity, all of which are the basic conditions in ADHD (18)(19)(20).…”
Section: Hemofilili çOcuk Ve Ergenlerde Eklem İçi Kanamalar İle Dikkamentioning
confidence: 99%
See 1 more Smart Citation
“…People with ADHD are also more prone to injuries and accidents, including serious injuries and traffic accidents, than those without ADHD [18, 31, 51]. Other associations with ADHD include substance abuse problems and interactions with the criminal justice system [32, 48, 52].…”
Section: Introductionmentioning
confidence: 99%
“…DiScala et al 13 reported that children with ADHD symptoms had increased risk for injuries to multiple body regions and head injuries. It has been reported that higher risk of injuries in patients with ADHD could be related to hyperactivity, inattentiveness, and risk-taking behaviour 14 15…”
Section: Discussionmentioning
confidence: 99%